2022
DOI: 10.1093/jacamr/dlac130
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on multidrug-resistant organisms causing healthcare-associated infections: a narrative review

Abstract: Coronavirus disease 2019 (COVID-19) changed healthcare across the world. With this change came an increase in healthcare-associated infections (HAIs) and a concerning concurrent proliferation of MDR organisms (MDROs). In this narrative review, we describe the impact of COVID-19 on HAIs and MDROs, describe potential causes of these changes, and discuss future directions to combat the observed rise in rates of HAIs and MDRO infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 109 publications
0
26
0
Order By: Relevance
“…The use of Personal Protective Equipment (PPE), which was meant to protect healthcare staff and reduce infection, led to suboptimal utilization and disease transmission. 6,38 Third, host factors, including older ages, and comorbidities, facilitate the risk of MDR, as reported previously. 39 In this study, the optimal COV of NLR was demonstrated to differentiate between COVID-19 with and without SPBI.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The use of Personal Protective Equipment (PPE), which was meant to protect healthcare staff and reduce infection, led to suboptimal utilization and disease transmission. 6,38 Third, host factors, including older ages, and comorbidities, facilitate the risk of MDR, as reported previously. 39 In this study, the optimal COV of NLR was demonstrated to differentiate between COVID-19 with and without SPBI.…”
mentioning
confidence: 60%
“…[3][4][5] Previous studies reported increased morbidity and mortality due to secondary bacterial infection. 6 The occurrence of secondary pulmonary bacterial infection (SPBI) was underpinned by three mechanisms, namely dysregulation of the immune response, dysbiosis of the respiratory tract microbiota, and damage to respiratory tract epithelial cells. 7,8 The management of COVID-19 has been impacted by issues related to SPBI, such as the high rate of hospitalization and prolonged hospital stays, which increase the risk of hospital-acquired infection.…”
Section: Introductionmentioning
confidence: 99%
“…These conflicting reports suggest that impacts of COVID-19 on antibiotic resistance likely depend on the particular population, setting, and bacteria in question and may be highly context specific. Several international studies have now reported on rates of healthcare-associated infection during the pandemic [ 12 , 13 ], but few have reported data on bacterial colonization or transmission, on rates of antibiotic resistance among colonized patients, nor on the putative mechanisms driving potential pandemic-related shits in antibiotic resistance epidemiology [ 14 ]. Mathematical modelling is a useful tool to help disentangle the mechanisms linking the transmission dynamics of co-occurring pathogens, especially when data are limited.…”
Section: Introductionmentioning
confidence: 99%
“…14,24 The COVID-19 pandemic has led to a significant increase in hospital-acquired MDRO rates in many regions. 25 According to the CDC, there has been a 78% increase in hospital-onset CRAB cases. 26 This increase is likely due to a variety of factors, including human factors such as staffing shortages, inadequate use of personal protective equipment, and poor hand hygiene compliance.…”
Section: Discussionmentioning
confidence: 99%